Asuhan Kebidanan Berkelanjutan pada Ny. L, Ny. U, Ny. LT di Praktik Mandiri Bidan (PMB) Purniawati di Desa Pujorahayu - Fauziah, Nur Alfi; Primadevi, Inggit; Qurniasih, Nila; Mayasari, Ade Tyas (Penerbit Goodwood, 2023)
Purpose: provide midwifery care on an ongoing basis to Mrs. L, Mrs. U and Mrs. LT from pregnancy, childbirth, BBL (new born), postpartum and family planning at the Purniawati Midwife Independent Practice in 2022. Method: subjects started from the third trimester of pregnancy, and family planning (KB) and babies. The place used in taking cases at PMB Purniawati and the residence of Ny. L, Mrs. U and Mrs. LT in Pujorahayu Village. The time for the study starts in March – April 2022. The method used in taking this case is descriptive observational. Result: When pregnant women feel anxious about labor and pain, yoga can help maintain the elasticity and strength of the pelvic muscles, so that pain will decrease and create calm so that anxiety can be reduced. The yoga intervention given also showed a correlation with Ny. L where in the process of giving birth Mrs. L was not worried when facing labor.